The Gentle Grafter - Henry, O., 1862-1910; Greening, Harry Cornell, 1876-1930?; Preston, May Wilson, 1873-1949 (Salt Lake City, UT : Project Gutenberg, 1999)
"The Gentle Grafter" by O. Henry is a collection of humorous short stories written in the early 20th century. The book revolves around the misadventures and schemes of the main character, Jeff Peters, and his partner, Andy Tucker, as they engage in a variety of con games and dubious enterprises, often with a light-hearted approach to their morally questionable activities. At the start of the book, the tone is set with a conversation between Jeff Peters and another character, showcasing Jeff's witty, philosophical reflections on their experiences with grafting and trusts. Through dialogue and storytelling, Jeff describes a scheme involving a flood-stricken town called Bird City, where he and Andy create a monopoly on the local saloons during a rainstorm, capitalizing on the desperate thirst of the townsfolk. The pair's antics introduce readers to the humor and cleverness that underpins their exploits, hinting at the satirical exploration of societal norms surrounding graft and capitalism that O. Henry is known for. (This is an automatically generated summary.)
The octopus marooned -- Jeff Peters as a personal magnet -- Modern rural sports -- The chair of philanthromathematics -- The hand that riles the world -- The exact science of matrimony -- A midsummer masquerade -- Shearing the wolf -- Innocents of Broadway -- Conscience in art -- The man higher up -- A tempered wind -- Hostages to Momus -- The ethics of pig.
Release date is 1999-07-01
E-text prepared by John Bickers and Dagny and revised by Joseph E. Loewenstein, M.D.
Keywords: Fiction; Humorous stories, American